A biocatalytic hydroxylation-enabled unified approach to C19-hydroxylated steroids - Junlin Wang; Yanan Zhang; Huanhuan Liu; Yong Shang; Linjun Zhou; Penglin Wei; Wen-Bing Yin; Zixin Deng; Xudong Qu; Qianghui Zhou (Nature Communications, 2019)
C19 hydroxylation is a unique feature of some bioactive steroids. Here, the authors developed a direct C19 hydroxylation approach to scalably access 19-OH-cortexolone in the host T. cucumeris and then converted the product into various pharmaceutically useful products via chemical synthesis.